2019
DOI: 10.15407/ukrbotj76.03.252
|View full text |Cite
|
Sign up to set email alerts
|

First records of Erysiphe corylacearum (Erysiphales, Ascomycota) on Corylus avellana in Ukraine

Abstract: Heluta V.P., Makarenko N.V., Al-Maali G. A. 2019. First records of Erysiphe corylacearum (Erysiphales, Ascomycota) on Corylus avellana in Ukraine. Ukrainian Botanical Journal, 76(3): 252-259. Abstract. Information on the records of a new adventive powdery mildew fungus Erysiphe corylacearum (Erysiphales, Ascomycota) in Ukraine is provided. The fungus was found on Corylus avellana (Betulaceae) in Kyiv, as well as in Crimea. Current distribution of this species outside its primary range is analyzed. It has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
2
12
0
3
Order By: Relevance
“…Erysiphe corylacearum is native to east Asia and has been reported from USA (Ohio) and Canada but until now it has been unknown from central Europe (Braun & Cook 2012). Recently, Heluta et al (2019) reported its occurrence on C. avellana from Ukraine, but without molecular validation. The species has been reported as an invasive pathogen from hazelnut orchards in Turkey, Iran and Georgia where it caused serious damage (Arzanlou et al ., 2018, Meparishvili et al ., 2019).…”
Section: Figurementioning
confidence: 99%
“…Erysiphe corylacearum is native to east Asia and has been reported from USA (Ohio) and Canada but until now it has been unknown from central Europe (Braun & Cook 2012). Recently, Heluta et al (2019) reported its occurrence on C. avellana from Ukraine, but without molecular validation. The species has been reported as an invasive pathogen from hazelnut orchards in Turkey, Iran and Georgia where it caused serious damage (Arzanlou et al ., 2018, Meparishvili et al ., 2019).…”
Section: Figurementioning
confidence: 99%
“…Microscopic examination showed that all studied Carpathian specimens belong to Erysiphe corylacearum and are morphologically very close to those previously collected in Kyiv. However, like the Kyiv materials [Heluta et al, 2019], they are slightly different from the Far Eastern samples. The fungus from the Carpathians also has somewhat larger fruit bodies; consequently, the ratio between the length of the appendage and the diameter of the chasmothecium varies, and therefore, the appendages seem shorter (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Erysiphe corylacearum, unlike the rest of the alien species listed above, is an East Asian-North American fungus because it has been recorded in both continents [Braun, 1982;Braun, Cook, 2012;Bunkina, 1991;Heluta, 1991;Heluta et al, 2019;Salmon, 1900]. Its recent findings in outside of the primary distribution range, viz.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations